Proces fúzí obchodních společností v právních, účetních a daňových souvislostech - Sedláček, Jaroslav (Masaryk University Press, 2020)
Publication summarizes the main results of the research project. The theoretical findings are verified empirically on a sample of companies included in its own database created in the research project. Economic data from the financial statements of companies in the Czech Republic, which merged in the past 10 years, are statistically evaluated and subjected to debate. The first part is devoted to the historical development of mergers and their importance in the global and national economy. The following chapters present the results of the survey of motivation of mergers in the Czech region, discussion of the issues arising from the legislation at transformation of companies and comparison of accounting methods Czech accounting rules, international rules (IFRS) and the accounting principles (U.S. GAAP). The final chapter on tax aspects of mergers provides recommendations for reducing administrative burden and tax problems with the mergers. The book is suitable for scientists, specialized companies and professionals who work in the transformation of companies.